PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII4 SMP MUHAMMADIYAH 1 PEKANBARU - Mega Afrianti; Jalinus Jalinus; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is a class action research that aims to improve the learning process and increase learning result of mathematics in grade VII4 SMP Muhammadiyah 1 Pekanbaru by applying the contextual approuch. The subject of this research were the students in the class VII4 SMP Muhammadiyah 1 Pekanbaru that consist of 14 boys and 11 girls at the first semester of academic year 2017/2018. Implementation of the learning process before action to be held, there is a problem of learning that is still focused on the teacher so that students can not find the learning concept and construct their knowledge by themselves. To solve this problem requires a learning approuch where students can actively discover learning concepts so that they can construct their knowledge. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed in desciptive narative, while the students’ mathematic tests were analyzed in statistic desciptive. The descriptive showed an improvement of learning process prior to the action on the first and second cycles. The percentage of students who achieve minimum mastery before the action is 28%, at first cycles is 48% and at second cycles is 72%. The result of the research showed that implementation of contextual approuch can improve the learning process and increased the student’s achievement of learning mathematic in grade VII4 SMP Muhammadiyah 1 Pekanbaru in the first semester academic years 2017/2018.Keywords : Student’s Math Achievement, Contextual approuch, Clasroom Action Research.